Modified layered positive electrode material, preparation method thereof and sodium ion battery containing modified layered positive electrode material

Through Y element doping and Na2TiO3 layer coating technology, the structural stability and cycling performance of NaNi1/3Fe1/3Mn1/3O2 positive electrode material are improved, poor circulation performance and long-term storage problems are solved, and more efficient sodium ion battery applications are achieved.

CN119650637APending Publication Date: 2025-03-18BEI JING XI BEI DONG LI KE JI YOU XIAN GONG SI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411810191.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

O3-phase layered transition metal oxide positive electrode material has problems in circulating performance and long-term storage. It has poor circulation performance and is easy to react with moisture and carbon dioxide in the air, resulting in a decrease in structural stability.

Method used

Through Y element doping and surface coating of Na2TiO3 layer, the structural stability of the NaNi1/3Fe1/3Mn1/3O2 positive electrode material is enhanced, and air is isolated to prevent reaction with moisture and carbon dioxide.

Benefits of technology

It significantly improves the circulation performance of the positive electrode material, solves the problem of long-term storage, and ensures the stability and application value of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650637A_ABST
    Figure CN119650637A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery positive electrode materials, in particular to a modified layered positive electrode material, a preparation method thereof and a sodium ion battery containing the modified layered positive electrode material. The Fe element in the NaNi1 / 3Fe1 / 3Mn1 / 3O2 material is partially replaced by the Y element, so that the structural stability of the material is improved, and the cycle performance of the O3 type layered positive electrode material is effectively improved; meanwhile, the surface of the O3 type layered positive electrode material is coated with a Na2TiO3 layer, so that doping of the NaNi < 1 / 3 > Fe < 1 / 3-x > Mn < 1 / 3 > Y < x > O < 2 > material by a titanium element is realized, the NaNi < 1 / 3 > Fe < 1 / 3-x > Mn < 1 / 3 > Y < x > O < 2 > material can be isolated from air, the NaNi < 1 / 3 > Fe < 1 / 3-x > Mn < 1 / 3 > Y < x > O < 2 > material is prevented from reacting with moisture and carbon dioxide in the air, and the problem that the material cannot be stored for a long time in the air is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a modified layered positive electrode material, a preparation method thereof, and a sodium ion battery comprising the same. Background Art

[0002] The current widely studied cathode materials for sodium-ion batteries mainly focus on polyanionic compounds, Prussian blue analogs and layered transition metal oxides. Among these three, layered transition metal oxides stand out due to their simple synthesis process, excellent conductivity, low toxicity and high theoretical specific capacity. In particular, cobalt-free O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Since its report, O2 materials have attracted great interest from researchers due to their high capacity, low cost and environmental friendliness. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode material, and hard carbon as the negative electrode material, successfully assembled a soft pack battery, and developed the world's first preliminary model of a sodium ion battery energy storage system. This major achievement fully demonstrates the NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 has great potential and application value as a positive electrode material for future commercial sodium-ion batteries.

[0003] However, the common problems of O3-phase layered transition metal oxides still hinder their commercialization. First, their cycle performance is poor. The slip of the transition metal layer during charging and discharging will lead to complex irreversible phase changes, which will weaken the structural stability and affect the cycle performance. Secondly, O3-type oxides have a sodium-rich structure and are easily reacted with moisture and carbon dioxide in the air, which destroys their structure and makes them difficult to store for a long time.

[0004] Therefore, how to provide a NaNi with good cycle performance and long-term storage through reasonable modification? 1 / 3 Fe 1 / 3Mn 1 / 3 O2 positive electrode materials have become a problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a modified layered positive electrode material, a preparation method thereof and a sodium ion battery comprising the same. The modified layered positive electrode material effectively improves the NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3The cycling performance of O2 positive electrode materials has been improved, and the problem that it cannot be stored in the air for a long time has been improved, which has promoted its application in sodium-ion batteries.

[0006] In a first aspect, the present disclosure provides a modified layered positive electrode material, the modified layered positive electrode material comprising an O3-type layered positive electrode material, and a Na2TiO3 layer coated on the surface of the O3-type layered positive electrode material;

[0007] The chemical formula of the O3 type layered cathode material is:

[0008] NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where 0<x≤0.02;

[0009] Exemplarily, x is selected as 0.01, 0.015 or 0.02, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0010] The present invention discloses that by combining the Y element with NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The Fe element in the O2 material is partially replaced, which improves its structural stability, thereby effectively improving the cycle performance of the O3 type layered positive electrode material; at the same time, by coating the Na2TiO3 layer on its surface, not only the titanium element is 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x The doping of O2 materials can also make NaNi 1 / 3 Fe 1 / 3- x Mn 1 / 3 Y x O2 materials isolate the air and prevent it from reacting with moisture and carbon dioxide in the air, effectively improving the problem that it cannot be stored in the air for a long time.

[0011] In the modified layered cathode material disclosed in the present invention, the doping amount of the Y element should not be too high, otherwise it will reduce the redox couple (Fe 3+ / Fe 4+ ) content, which in turn affects the energy density of the system.

[0012] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.

[0013] As a preferred technical solution of the present invention, in the modified layered positive electrode material, the content of the O3 type layered positive electrode material is 93-99wt%, for example, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%, etc.; the content of the Na2TiO3 layer is 1-7wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt% or 7wt%, etc., but is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0014] In the present disclosure, a suitable raw material ratio is helpful to improve the comprehensive performance of the modified layered positive electrode material. If the content of the Na2TiO3 layer is too much, it will hinder the Na + The transmission to the surface of the positive electrode material affects the ionic conductivity of the material, thereby reducing the rate performance of the battery; if the content of the Na2TiO3 layer is too little, it cannot effectively prevent the direct contact between moisture and carbon dioxide in the air and the positive electrode material, and cannot achieve the purpose of improving the stability of the material in the air.

[0015] As a preferred technical solution of the present disclosure, the particle size of the O3 type layered positive electrode material is 0.3-1.7μm, for example, 0.3μm, 0.5μm, 0.7μm, 1μm, 1.2μm, 1.5μm or 1.7μm, but is not limited to the listed values, and other unlisted values ​​within the above range are also applicable.

[0016] In a second aspect, the present disclosure provides a method for preparing the modified layered positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0017] (1) mixing a first sodium source, a nickel source, an iron source, a manganese source and a yttrium source with a first solvent, and then performing a first sintering to obtain an O3 type layered positive electrode material;

[0018] (2) The obtained O3-type layered cathode material is liquid-phase coated with a Na2TiO3 precursor solution, and then subjected to a second sintering to obtain a modified layered cathode material.

[0019] The preparation method firstly prepares an O3 type layered positive electrode material by a solid phase sintering method, and then coats the surface of the O3 type layered positive electrode material with a Na2TiO3 material by a liquid phase coating method to achieve NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The modification of O2 has a simple preparation process and is conducive to industrial production.

[0020] As a preferred technical solution of the present disclosure, in step (1), the first sodium source includes one or more of sodium acetate, sodium carbonate, sodium nitrate, sodium oxalate, sodium bicarbonate or sodium citrate, such as a combination of sodium carbonate and sodium oxalate, a combination of sodium carbonate and sodium acetate, etc.

[0021] When sodium carbonate is selected as the first sodium source, in order to prevent sodium carbonate from volatilizing during the sintering process and affecting the final element ratio of the material, sodium carbonate needs to be added in excess. Generally, a molar excess of 3% is sufficient.

[0022] Preferably, the nickel source in step (1) comprises nickel oxide.

[0023] Preferably, the iron source in step (1) comprises iron oxide.

[0024] Preferably, the manganese source in step (1) comprises manganese oxide.

[0025] Preferably, the yttrium source in step (1) comprises yttrium oxide.

[0026] Preferably, in step (1), the first solvent comprises ethanol.

[0027] As a preferred technical solution of the present disclosure, the mixing method in step (1) includes ball milling.

[0028] Preferably, the ball-to-material mass ratio of the ball mill is (5-8):1, such as 5:1, 6:1, 7:1 or 8:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0029] Preferably, a first drying is performed between the mixing in step (1) and the first sintering.

[0030] Preferably, the first drying temperature is 80-100°C, such as 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0031] Preferably, the temperature of the first sintering in step (1) is 800-1000°C, such as 800°C, 850°C, 900°C, 950°C or 1000°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0032] Preferably, the first sintering time in step (1) is 15-20 h, for example, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0033] Preferably, the heating rate of the first sintering in step (1) is 3-7°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min or 7°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0034] As a preferred technical solution of the present disclosure, step (2) includes: mixing a second sodium source, a titanium source and a reducing agent with a second solvent to obtain a Na2TiO3 precursor solution; mixing the Na2TiO3 precursor solution with the O3 type layered positive electrode material, stirring until the liquid evaporates, and then sequentially performing a second drying and a second sintering to obtain a modified layered positive electrode material.

[0035] Preferably, step (2) comprises: mixing a second sodium source with a second solvent, then adding a titanium source and stirring for 10-15 minutes, and then adding a reducing agent and stirring for 40-60 minutes to obtain a Na2TiO3 precursor solution; mixing the Na2TiO3 precursor solution with the O3-type layered positive electrode material, stirring until the liquid evaporates, and then sequentially performing a second drying and a second sintering to obtain a modified layered positive electrode material.

[0036] As a preferred technical solution of the present disclosure, the second sodium source includes sodium acetate.

[0037] Preferably, the titanium source comprises tetrabutyl titanate.

[0038] Preferably, the reducing agent comprises citric acid.

[0039] Preferably, the molar ratio of the sodium in the second sodium source, the titanium in the titanium source and the reducing agent is 2:1:(1-1.2), for example 2:1:1, 2:1:1.05, 2:1:1.1, 2:1:1.15 or 2:1:1.2, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Preferably, the second solvent comprises ethanol.

[0041] As a preferred technical solution of the present disclosure, the stirring temperature is 50-70°C, such as 50°C, 55°C, 60°C, 65°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0042] Preferably, the second drying temperature is 80-100°C, such as 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0043] Preferably, the second sintering temperature is 600-800°C, such as 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0044] In a third aspect, the present disclosure provides a sodium ion battery, comprising the modified layered positive electrode material as described in the first aspect, or the modified layered positive electrode material prepared by the preparation method as described in the second aspect.

[0045] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0046] The present invention discloses that by combining the Y element with NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The Fe element in the O2 material is partially replaced, which improves its structural stability, thereby effectively improving the cycle performance of the O3 type layered positive electrode material; at the same time, by coating the surface of the O3 type layered positive electrode material described in the present disclosure with a Na2TiO3 layer, not only the titanium element is used to replace the NaNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x The doping of O2 materials can also make NaNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2 materials isolate the air and prevent it from reacting with moisture and carbon dioxide in the air, effectively improving the problem that it cannot be stored in the air for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0049] Figure 1 This is a SEM image of the modified layered positive electrode material described in Example 2 of the present disclosure;

[0050] Figure 2 This is an EDS image of the modified layered positive electrode material described in Example 2 of the present disclosure;

[0051] Figure 3This is a SEM image of the layered positive electrode material described in Comparative Example 1 of the present disclosure;

[0052] Figure 4 This is a comparison chart of the cycle performances of the modified layered positive electrode material described in Example 2 of the present disclosure, the layered positive electrode material described in Comparative Example 1, and the modified layered positive electrode material described in Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION

[0053] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0054] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0055] Example 1

[0056] This embodiment provides a modified layered positive electrode material and a preparation method thereof, wherein the modified layered positive electrode material comprises an O3-type layered positive electrode material and a Na2TiO3 layer coated on the surface of the O3-type layered positive electrode material;

[0057] The chemical formula of the O3 type layered cathode material is:

[0058] NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where x = 0.01.

[0059] The content of the O3 type layered positive electrode material is 95wt%, and the content of the Na2TiO3 layer is 5wt%;

[0060] The average particle size of the O3 type layered positive electrode material is 1 μm.

[0061] The preparation method comprises:

[0062] (1) Sodium carbonate, nickel oxide, iron oxide, manganese oxide, and yttrium oxide were mixed with ethanol in a ball mill according to a stoichiometric ratio, with a ball-to-material mass ratio of 5:1, and the mixture was ball-milled for 10 hours to obtain a mixture; the obtained mixture was then dried at 80° C. for 12 hours, and then sintered at 900° C. for 15 hours, with the sintering heating rate controlled at 5° C. / min, and ground after natural cooling to obtain an O3-type layered positive electrode material with an average particle size of 1 μm;

[0063] (2) preparing a Na2TiO3 precursor solution by mixing sodium acetate, tetrabutyl titanate and citric acid in a molar ratio of 2:1:1, wherein the specific operation includes: dissolving sodium acetate in an ethanol solution, then adding tetrabutyl titanate and stirring for 10 minutes, and then adding citric acid and stirring for 40 minutes to obtain a Na2TiO3 precursor solution;

[0064] Then, the Na2TiO3 precursor solution was mixed with the O3-type layered cathode material obtained in step (1), stirred at 60°C until the liquid evaporated, then dried at 80°C for 12h, sintered at 700°C for 6h, and naturally cooled to room temperature to obtain a modified layered cathode material.

[0065] Example 2

[0066] This embodiment provides a modified layered positive electrode material and a preparation method thereof, wherein the modified layered positive electrode material comprises an O3-type layered positive electrode material and a Na2TiO3 layer coated on the surface of the O3-type layered positive electrode material;

[0067] The chemical formula of the O3 type layered cathode material is:

[0068] NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where x = 0.02.

[0069] The content of the O3 type layered positive electrode material is 93wt%, and the content of the Na2TiO3 layer is 7wt%;

[0070] The average particle size of the O3 type layered positive electrode material is 1 μm.

[0071] The preparation method comprises:

[0072] (1) Sodium carbonate, nickel oxide, iron oxide, manganese oxide, and yttrium oxide were mixed with ethanol in a ball mill according to a stoichiometric ratio, with a ball-to-material mass ratio of 5:1, and the mixture was ball-milled for 11 hours to obtain a mixture; the obtained mixture was then dried at 90° C. for 12 hours, and then sintered at 1000° C. for 15 hours, with the sintering heating rate controlled at 5° C. / min, and then ground after natural cooling to obtain an O3-type layered positive electrode material with an average particle size of 1 μm;

[0073] (2) sodium acetate, tetrabutyl titanate and citric acid are prepared into a Na2TiO3 precursor solution in a molar ratio of 2:1:1.1. The specific operation includes:

[0074] Sodium acetate was dissolved in an ethanol solution, and then tetrabutyl titanate was added and stirred for 10 minutes, and then citric acid was added and stirred for 40 minutes to obtain a Na2TiO3 precursor solution;

[0075] The Na2TiO3 precursor solution was mixed with the O3-type layered cathode material obtained in step (1), stirred at 70°C until the liquid evaporated, then dried at 85°C for 12h, sintered at 800°C for 6h, and naturally cooled to room temperature to obtain a modified layered cathode material.

[0076] The SEM image of the modified layered cathode material is shown in Figure 1 As shown. Figure 2 The white box in (a) was analyzed by element analysis to obtain the EDS diagram. Figure 2 As shown. Figure 2 It can be seen that Na, Ni, Fe, Mn, O, Ti and Y elements are evenly distributed in the sample, indicating the uniformity of the Na2TiO3 coating distribution; in addition, since the content of Y element is relatively low compared with other elements, the signal is weak. The uniform distribution of Y element in the material also indicates that Y 3+ It has been successfully integrated into the crystal structure.

[0077] Example 3

[0078] This embodiment provides a modified layered positive electrode material and a preparation method thereof, wherein the modified layered positive electrode material comprises an O3-type layered positive electrode material and a Na2TiO3 layer coated on the surface of the O3-type layered positive electrode material;

[0079] The chemical formula of the O3 type layered cathode material is:

[0080] NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where x = 0.15.

[0081] The content of the O3 type layered positive electrode material is 99wt%, and the content of the Na2TiO3 layer is 1wt%;

[0082] The average particle size of the O3 type layered positive electrode material is 1 μm.

[0083] The preparation method comprises:

[0084] (1) Sodium carbonate, nickel oxide, iron oxide, manganese oxide, yttrium oxide and ethanol were mixed in a ball mill according to a stoichiometric ratio, with a ball-to-material mass ratio of 5:1, and the mixture was ball-milled for 11 hours to obtain a mixture; the obtained mixture was then dried at 85° C. for 12 hours, and then sintered at 800° C. for 17 hours, with the sintering heating rate controlled at 7° C. / min, and ground after natural cooling to obtain an O3-type layered positive electrode material with an average particle size of 1 μm;

[0085] (2) preparing a Na2TiO3 precursor solution by mixing sodium acetate, tetrabutyl titanate and citric acid in a molar ratio of 2:1:1, wherein the specific operation includes: dissolving sodium acetate in an ethanol solution, then adding tetrabutyl titanate and stirring for 15 minutes, and then adding citric acid and stirring for 45 minutes to obtain a Na2TiO3 precursor solution;

[0086] Then, the Na2TiO3 precursor solution was mixed with the O3-type layered cathode material obtained in step (1), stirred at 70°C until the liquid evaporated, then dried at 85°C for 12h, sintered at 600°C for 7h, and naturally cooled to room temperature to obtain a modified layered cathode material.

[0087] Example 4

[0088] This embodiment provides a modified layered positive electrode material and a preparation method thereof. The modified layered positive electrode material refers to the modified layered positive electrode material in Example 2, except that:

[0089] In the modified layered positive electrode material, the content of the O3 type layered positive electrode material is 90wt%, and the content of the Na2TiO3 layer is 10wt%.

[0090] Comparative Example 1

[0091] This comparative example provides a layered positive electrode material, wherein the layered positive electrode material comprises an O3-type layered positive electrode material, and the chemical formula of the O3-type layered positive electrode material is:

[0092] NeNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2;

[0093] The average particle size of the O3 type layered positive electrode material is 1 μm.

[0094] The SEM image of the layered positive electrode material in this comparative example is as follows Figure 3 shown.

[0095] Comparative Example 2

[0096] This comparative example provides a modified layered positive electrode material and a preparation method thereof, wherein the layered positive electrode material comprises an O3-type layered positive electrode material, and the chemical formula of the O3-type layered positive electrode material is:

[0097] NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where x = 0.01.

[0098] The average particle size of the O3 type layered positive electrode material is 1 μm.

[0099] The preparation method is similar to the preparation method in Example 1, except that step (2) only comprises: sintering the O3-type layered positive electrode material obtained in step (1) at 700°C for 6 hours at a heating rate of 5°C / min. -1 , naturally cooled to room temperature, and then ground to obtain a modified layered positive electrode material.

[0100] Comparative Example 3

[0101] This comparative example provides a modified layered positive electrode material and a preparation method thereof, wherein the layered positive electrode material comprises an O3-type layered positive electrode material and a Na2TiO3 layer coated on the surface of the O3-type layered positive electrode material;

[0102] The chemical formula of the O3-type layered cathode material is: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2;

[0103] The content of the O3 type layered positive electrode material is 95wt%, and the content of the Na2TiO3 layer is 5wt%;

[0104] The average particle size of the O3 type layered positive electrode material is 1 μm.

[0105] The preparation method is similar to the preparation method in Example 1, with the only difference being that yttrium oxide is not added in step (1), that is, no doping with the Y element is performed.

[0106] Comparative Example 4

[0107] This embodiment provides a modified layered positive electrode material and a preparation method thereof. The modified layered positive electrode material refers to the modified layered positive electrode material in Example 2, except that the chemical formula of the O3-type layered positive electrode material is:

[0108] NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where x = 0.04.

[0109] And the average particle size of the O3 type layered positive electrode material is 1 μm.

[0110] The preparation method is similar to the preparation method in Example 2, except that: step (1) adds raw materials according to the chemical formula of the above-mentioned O3-type layered positive electrode material.

[0111] Performance Test:

[0112] Assemble the button cell battery for testing:

[0113] Positive electrode sheet: The positive electrode material to be tested, conductive carbon black and binder (PVDF) were weighed into an agate mortar in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added thereto while grinding. During the grinding process, an infrared lamp was turned on for baking until the slurry was slightly fluid when the mortar was tilted and there were no obvious large particles. At this time, the ground slurry was transferred to aluminum foil for uniform coating, and then the coated aluminum foil was transferred to a vacuum oven for drying for 12 hours to obtain a positive electrode sheet; it was cut into a positive electrode sheet with a diameter of 11 mm by punching, and the loading amount of active material on the positive electrode sheet was 1.5 mg / cm 2 ;

[0114] Negative electrode: metallic sodium with a diameter of 11 mm;

[0115] Diaphragm: Whatman GF / C type glass fiber;

[0116] Electrolyte: Propylene carbonate (PC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC) were mixed in a volume ratio of 50:48:2, and then 1 mol / L NaPF6 was added and mixed evenly to prepare an electrolyte;

[0117] The above components were assembled into button-type batteries, which were packaged by a sealing machine and placed in a constant temperature box at 25°C for 12 hours before the electrochemical performance test was performed.

[0118] Referring to the above-mentioned method for preparing button batteries, button batteries were prepared using the positive electrode materials of Examples 1-4 and Comparative Examples 1-4 as the positive electrode materials to be tested, and their gram capacity after 200 cycles was tested, and the capacity retention rate was calculated. The test conditions were: temperature of 25°C, discharge rate of 0.2C, and discharge voltage range of 2-4V. The results are shown in Table 1.

[0119]

[0120] The cycle performance comparison of button batteries obtained in Example 2 and Comparative Examples 1-3 is shown in the figure below: Figure 4 As shown. Figure 4 It can be seen that the use of the modified layered positive electrode material disclosed in the present invention can effectively improve the cycle performance of sodium ion batteries.

[0121] Table 1

[0122]

[0123] As can be seen from Table 1, the sodium ion batteries prepared by using the modified layered positive electrode materials disclosed in Examples 1-4 can effectively improve their cycle performance, and the capacity retention rate of 200 cycles at a rate of 0.2C is more than 82.85%; and by controlling the amount of Y element doping and the content of the coating layer, the cycle performance is further improved, so that the capacity retention rate of 200 cycles at a rate of 0.2C is more than 83.88%.

[0124] In Comparative Example 1, no Y element is doped and no Na2TiO3 layer is coated, resulting in severe capacity decay and poor cycle performance.

[0125] In Comparative Example 2, only Y element is doped, and no Na2TiO3 layer is coated; and in Comparative Example 3, only Na2TiO3 layer is coated, and no Y element is doped. Although the cyclability of the two has been improved to a certain extent compared with Comparative Example 1, the improvement is still limited compared with Examples 1-4. It can be seen that the present disclosure, through the doping of Y element and the coating of Na2TiO3 layer, the two synergistically exert the effect of "1+1>2", greatly improving the cycle performance of the positive electrode material.

[0126] In Comparative Example 4, excessive doping of the Y element causes a decrease in its cycle performance.

[0127] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0128] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A modified layered positive electrode material, characterized in that: The modified layered positive electrode material comprises an O3 type layered positive electrode material and a Na2TiO3 layer coated on the surface of the O3 type layered positive electrode material; The chemical formula of the O3 type layered cathode material is: NeNi 1 / 3 Fe 1 / 3-x Mn 1 / 3 Y x O2, where 0<x≤0.

02.

2. The modified layered positive electrode material according to claim 1, characterized in that In the modified layered positive electrode material, the content of the O3 type layered positive electrode material is 93-99wt%, and the content of the Na2TiO3 layer is 1-7wt%.

3. The modified layered positive electrode material according to claim 1 or 2, characterized in that: The particle size of the O3 type layered positive electrode material is 0.3-1.7 μm.

4. A method for preparing a modified layered positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a first sodium source, a nickel source, an iron source, a manganese source and a yttrium source with a first solvent, and then performing a first sintering to obtain an O3 type layered positive electrode material; (2) The obtained O3-type layered cathode material is liquid-phase coated with a Na2TiO3 precursor solution, and then subjected to a second sintering to obtain a modified layered cathode material.

5. The preparation method according to claim 4, characterized in that: Step (1) the first sodium source comprises one or more of sodium acetate, sodium carbonate, sodium nitrate, sodium oxalate, sodium bicarbonate or sodium citrate; Preferably, the nickel source in step (1) comprises nickel oxide; Preferably, the iron source in step (1) comprises iron oxide; Preferably, the manganese source in step (1) comprises manganese oxide; Preferably, the yttrium source in step (1) comprises yttrium oxide; Preferably, in step (1), the first solvent comprises ethanol.

6. The preparation method according to claim 4 or 5, characterized in that: The mixing method in step (1) includes ball milling; Preferably, the ball-to-material mass ratio of the ball mill is (5-8):1; Preferably, a first drying is performed between the mixing in step (1) and the first sintering; Preferably, the first drying temperature is 80-100°C; Preferably, the temperature of the first sintering in step (1) is 800-1000° C.; Preferably, the first sintering time in step (1) is 15-20 hours; Preferably, the heating rate of the first sintering in step (1) is 3-7°C / min.

7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (2) comprises: mixing a second sodium source, a titanium source and a reducing agent with a second solvent to obtain a Na2TiO3 precursor solution; mixing the Na2TiO3 precursor solution with the O3-type layered positive electrode material, stirring until the liquid evaporates, and then sequentially performing a second drying and a second sintering to obtain a modified layered positive electrode material.

8. The preparation method according to claim 7, characterized in that: The second sodium source comprises sodium acetate; Preferably, the titanium source comprises tetrabutyl titanate; Preferably, the reducing agent comprises citric acid; Preferably, the molar ratio of the sodium in the second sodium source, the titanium in the titanium source and the reducing agent is 2:1:(1-1.2); Preferably, the second solvent comprises ethanol.

9. The preparation method according to claim 7 or 8, characterized in that: The stirring temperature is 50-70°C; Preferably, the second drying temperature is 80-100°C; Preferably, the second sintering temperature is 600-800°C.

10. A sodium ion battery, characterized in that: It comprises the modified layered positive electrode material as described in any one of claims 1 to 3, or the modified layered positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.

Citation Information

Cited By

  • Preparation method of sodium electrode layered oxide positive electrode material

    CN121583888A